Capital punishment : strategies for abolition - Hodgkinson, Peter (Director of the Centre for Capital Punishment Studies); Schabas, William, 1950- (Cambridge University Press, 2004)
What are the critical factors that determine whether a country replaces, retains or restores the death penalty? Why do some countries maintain the death penalty in theory but in reality rarely invoke it? This book seeks to identify the core issues that influence governments when formulating policy on capital punishment.